1974
DOI: 10.1159/000208245
|View full text |Cite
|
Sign up to set email alerts
|

Factor X Survival and Therapeutic Factor X Levels in the Abnormal Factor X (Factor X Friuli) Coagulation Disorder

Abstract: In two patients with the abnormal factor X (factor X Friuli) coagulation disorder a multiple tooth extraction was carried out immediately after the transfusion. X of 4 U of factor X concentrate (Bebulin) equivalent to 2,000 ml of normal plasma. No bleeding was noted. The half-life of the exogeneous component was 30 and 28 h, respectively. Two other patients with this peculiar disorder were treated with repeated whole blood, plasma and factor X concentrates for hematuria and posttraumatic fracture of the left z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1975
1975
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
(18 reference statements)
1
15
0
Order By: Relevance
“…This observation is in agreement with in vitro data which indicate that these patients lack inhibitors in their plasma [6]. It is interesting to note that similar results have been obtained by us in another abnor mality of the prothrombin complex factors, namely factor X Friuli disorder [4], The survival times observed are well in line with those reported in the literature [1,2,[8][9][10][11][12]. However, it is worth mentioning that some of the studies carried out dealt with the infu sion of large quantities of plasma which made all but impossible to calculate a satis factory half-life.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is in agreement with in vitro data which indicate that these patients lack inhibitors in their plasma [6]. It is interesting to note that similar results have been obtained by us in another abnor mality of the prothrombin complex factors, namely factor X Friuli disorder [4], The survival times observed are well in line with those reported in the literature [1,2,[8][9][10][11][12]. However, it is worth mentioning that some of the studies carried out dealt with the infu sion of large quantities of plasma which made all but impossible to calculate a satis factory half-life.…”
Section: Discussionsupporting
confidence: 92%
“…Materials and methods have been described in detail elsewhere [3][4][5][6], Factor VII level was as sayed as previously reported using a rabbit brain and a lung thromboplastin preparation and factor-VII-deficient plasma as substrate [5,6]. To calculate the exogenous fraction, 9 or 10°/o were subtracted from each reading for case 1 and case 2, respectively.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…One explanation of such a synergistic effect is that the prothrombin complex concentrates provide increased levels of prothrombin and or factor X that serve to enhance thrombin generation by factor VIIa [19,20]. Because the half-life of factor X in humans is as long as 30 hr [21], ongoing treatment with prothrombin complex concentrates may be unnecessary to obtain this synergistic response.…”
Section: Discussionmentioning
confidence: 99%
“…The half-life for our three cases (greater than 24 hr, 38.6 hr, and 56 hr) agrees generally with those of previous reports. In the 2 cases of abnormal factor X disorder reported by Girolami et al (1974), the in vivo half-life was 30 and 28 hr. They maintain that, as in the abnormal factor IX in hemophilia, there is no inhibitory activity in abnormal factor X disorders.…”
Section: Therapymentioning
confidence: 96%
“…Rizza (1972) reported a hemostatic level greater than 10%, Bidwell et al (1972) a level between 10 and 40%, Okamoto et al (1967) 15-20% andSarup et al (1972) 15%. In abnormal factor X disorders, Girolami et al (1974) maintain that 45-50% is sufficient for hemostatis at the time of hematoma formation due to tooth extraction, hematuria, trauma, etc. With regard to the hemostatic level at the time of major surgery, Krieger et al (1977) have reported that in all diseases of coagulation abnormalities, the hemostatic level is 100% prior to surgery, greater than 60% 4 days postoperatively, and greater than 40% 8 days postoperatively.…”
Section: Therapymentioning
confidence: 99%